Violence within women's prisons and its implications on reintegration effectiveness - Hamja Hamja; Murtiningsih Kartini; Asep Susanto (Gema Wiralodra, 2024)
The involvement of women in various aspects of life, both socially and economically, has exposed the potential for criminal behaviour among women. This situation has led to the phenomenon of women's involvement in criminal acts commonly associated with men, such as robbery, murder, organized crime, and human trafficking. Poor social and economic conditions tend to be triggering factors and solid reasons for women to engage in criminal activities. This background has become the basis for the increasing number of women in prison in Indonesia, opening the possibility of various forms of violence within women's prisons. This presents a significant challenge for the management of women's prisons in optimizing the reintegration system due to the escalation of significant demotivation resulting from the violence experienced by female inmates, both among themselves and with prison staff. This research employs an exploratory qualitative approach, focusing on women involved in criminal cases and sentenced to prison. Primary data from interview results are descriptively analysed, producing a comprehensive, authentic, and representative narrative. The findings of this study indicate that the concept of punishment in Indonesia still emphasizes punitive functions over corrective functions, where both physical and mental violence are considered effective forms of punishment, especially for women. Violence occurring within women's prisons is then negatively responded to and becomes a driving factor for the decreased interest of female inmates in succeeding in the reintegration program. This reluctance then triggers a negative response from the staff in the form of violence against female inmates. A solution to mitigate violence in women's prisons is the placement in open prisons, with the involvement of independent external parties in both the supervision process and the implementation of reintegration programs to achieve an inclusive and constructive effect for all parties involved.